Determinants of Product Quality on Customer Loyalty through Repurchase Intention and Customer Satisfaction at Kopi Kenangan - Sihombing, Rusman Efendi; Vitaharsa, Leonardo Indra; Pramadanti, Rindika (Yayasan Sinergi Kawula Muda, 2025)
The Target of this academic inquiry is to identify how the linkage between product quality and customer loyalty by considering the mediating roles of repurchase intention and customer satisfaction among customers of Kopi Kenangan in Bekasi City where the challenges currently faced are tight competition in the retail coffee industry, product quality as the main differentiator and changes in consumer behavior post-pandemic. This research uses a quantitative approach with the Structural Equation Modeling (SEM) method based on Partial Least Square (PLS) and data was collected through structured questionnaires. The sample in this academic inquiry consisted of 250 respondents selected using purposive sampling, specifically consumers who had made purchases more than once. The study found that product quality showed a statistically significant impact on repurchase intention is 0.805 (positive), customer satisfaction is 0.430 (positive), and customer loyalty is 0.453 (positive),. Moreover, repurchase intention and customer satisfaction were proven to act as mediating variables in the linkage between product quality and customer loyalty. These findings reinforce the importance of improving product quality as a strategic move to build customer satisfaction and customer loyalty in the coffee shop industry. This study strengthens the theory that repurchase intention and customer satisfaction are not only dependent variables between them, but also mutually reinforce the effect of product quality on customer loyalty and focus on local brands conducted in Bekasi City.